Iodido(N-phenylthiourea)bis(triphenylphosphine)copper(I) - Nimthong, Ruthairat (International Union of Crystallography, 2008)
The coordination geometry of the Cu atom in the title compound, [CuI(C(7)H(8)N(2)S)(C(18)H(15)P)(2)], is distorted tetrahedral; it is coordinated by two triphenylphosphine P atoms, one S atom from N-phenylthiourea (ptu) and one I atom. The crystal structure is stabilized by intra- and intermolecular N—H⋯I and N—H⋯S interactions.